(untitled) (Global Journal of Sciences, 2025)
This research explores the Ricci Inheritance Collineations (RICs) within cylindrically symmetric Marder type spacetimes. We categorize these spacetimes based on their RICs, examining both degenerate and non-degenerate Ricci tensor configurations. Through solving a system of coupled partial differential equations across thirteen distinct scenarios, we provide a thorough examination of inheritance symmetries. Our findings demonstrate the existence of infinite dimensional RICs in multiple cases, offering valuable insights into the geometric and physical characteristics of these spacetimes.